2011
DOI: 10.1111/j.1440-0960.2010.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoscopy of a minute melanoma

Abstract: We present a case report of a naevoid lentigo maligna (World Health Organisation level 1 melanoma) on the nose of a 46-year-old man. He was under surveillance because of a past history of two melanomas and developed a new lesion. The visible lesion was 1.6 mm in maximum diameter as measured by the scale on the dermatoscope footplate. The dermatoscopic structures present were limited to dots arranged asymmetrically. We believe that the fact that some of these dots were grey provided a useful clue to the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
0
16
1
1
Order By: Relevance
“…Previously the dermatoscopic features of an in-situ melanoma with a diameter of 1.6 mm were reported [7]. Published dermatoscopy images revealed that even at this minute size there was unequivocal asymmetry of structure and the presence of the dermatoscopic clue to melanoma of gray dots.…”
Section: Discussionmentioning
confidence: 99%
“…Previously the dermatoscopic features of an in-situ melanoma with a diameter of 1.6 mm were reported [7]. Published dermatoscopy images revealed that even at this minute size there was unequivocal asymmetry of structure and the presence of the dermatoscopic clue to melanoma of gray dots.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that small melanomas may not be asymmetrical [1,2]. It has also been reported that hyperpigmentation was the defining feature in all of 13 small melanomas (<4 mm diameter) in one series of 95 melanomas [12], but Pellizzari et al pointed out that this may in fact be due to selection bias, with darker lesions being discovered, while paler, hypomelanotic lesions may not be suspected at the stage where they are very small [2].…”
Section: Discussionmentioning
confidence: 99%
“…Small melanomas (diameter < 4 mm) present diagnostic difficulties, as the clinical and dermatoscopic characteristics of such lesions have been reported only rarely [1]. Another recent case report by Pellizzari et al suggests that in very small lesions chaos (asymmetry of structure or color) may not be unequivocally present [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gray structures, and more specifically gray circles, have been described as a clue to melanoma [7,8] correlating with extension of melanin-containing melanoma cells down hair follicles, and asymmetrically pigmented follicular openings are described as a clue to lentigo maligna [9]. Furthermore it has been recommended that the presence of any dermatoscopic gray structures on the face should lead to a biopsy [6]. …”
Section: Case Reportmentioning
confidence: 99%
“…Currently, few very small melanomas are diagnosed [4,5]. The increased use of dermatoscopy and digital monitoring should lead to more small melanomas being encountered [6]. What is not known is how commonly these very small melanomas, at the ‘infantile’ stage of Ackerman’s analogy, lack sufficient criteria to make the diagnosis of melanoma.…”
Section: Introductionmentioning
confidence: 99%